1978
DOI: 10.1139/y78-151
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iodine deficiency and propylthiouracil on the hypothalamo–pituitary–thyroid axis in the neonatal rat

Abstract: D u s s a u~~, J. H., and WALKER, P. 1978. The effect of iodine deficiency and propylthiouracil on the hypothalarno-pituitary-thyroid axis in the neonatal rat. Can. J. Physiol. Pharmacol. 56,[950][951][952][953][954][955] The efTect of chronic propylthiouracil (PTU) and low iodide diet (LID) on the development of the hypothala~no-pituitary-thyroid axis in the rat has been studied. Pregnant and neonatal rats received 0.05% PTU in their drinking water or LID (distilled water and LID: Teklad Mills, Madison, Wisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…together with a serum TSH level <5 pU/ ml, although still detectable. Persistently elevated TSH levels in spite of normal T4 and T3, especially if accompa nied by retardation in bone maturation, should be consid ered to indicate insufficient dosage or insufficient com pliance with therapy [2,69,70] rather than impairment of feedback control and reduced pituitary sensitivity to T4 resulting from hypothyroidism during fetal life [71], Follow-up of CH infants and children is routine. Clini cal examination, evaluation of growth including bone maturation [72], determination of scrum total and free T4 and T3 and TSH [73], as well as an evaluation of the psy chomotor and intellectual development will be performed at regular intervals.…”
Section: Treatment and Prognosis O F Permanent Sporadic Chmentioning
confidence: 99%
“…together with a serum TSH level <5 pU/ ml, although still detectable. Persistently elevated TSH levels in spite of normal T4 and T3, especially if accompa nied by retardation in bone maturation, should be consid ered to indicate insufficient dosage or insufficient com pliance with therapy [2,69,70] rather than impairment of feedback control and reduced pituitary sensitivity to T4 resulting from hypothyroidism during fetal life [71], Follow-up of CH infants and children is routine. Clini cal examination, evaluation of growth including bone maturation [72], determination of scrum total and free T4 and T3 and TSH [73], as well as an evaluation of the psy chomotor and intellectual development will be performed at regular intervals.…”
Section: Treatment and Prognosis O F Permanent Sporadic Chmentioning
confidence: 99%
“…The ovine species was not chosen for these studies since term AF rT3 concentrations are low in the sheep (8). Previously published rat (9)(10)(11)(12)(13)(14)(15)(16)(17) and primate (18,19) models of fetal hypothyroidism were not used since hypothyroidism had been induced at birth rather than in the fetus or combined maternal-fetal hypothyroidism resulted from the treatment regimen. When an effort was made to prepare isolated fetal hypothyroidism, pharmacologic doses of T4 were administered to dams receiving antithyroid drugs and/or a low-iodine diet (LID) (20).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal hypothyroidism, induced by iodine deficiency or administration of propylthiouracil (PTU), results in marked modifications in the ontogenetic pattern of the hypothalamic-pituitary-thyroid axis (3)(4)(5).…”
mentioning
confidence: 99%
“…Both Bakke et al (6,7) and Azizi et at. (8) have shown that rats rendered hyperthyroid during the neonatal period have significantly reduced serum T 4 and TSH concentrations as adults. Little is known, however, of the mechanism^) by which these modifications occur.…”
mentioning
confidence: 99%